"Eco-Efficient" Concrete incorporating Ceramic Waste powder and Red brick dust as an effective replacement for Ordinary Portland Cement and Fine aggregate. Issue 1 (November 2020) - Shanmugam, Durgadevi; Chinnasamy, Kavitha; kumar, Kathiravan Natrajan Sampath; Elangovan, Sankar; Raj, Jayakumar Poun
Abstract: Concrete is one of the most frequently used building material. Its usage worldwide is twice that of steel, wood, plastics and aluminum. Concrete is the mixture of cement, fine aggregate, coarse aggregate and water. The cement releases carbon-di-oxide which contributes 8% of annually released carbon content around the globe. The cement and fine aggregate in concrete can be partially or fully replaced by other cementitious materials. Ceramic waste powder is dumped away which brings about lot of ecological contamination and threatening both farming and general wellbeing. The cement is replaced with ceramic waste powder and red brick dust in replacement for fine aggregate in 5%, 10% and 15% by its weight. The mechanical and durability test were studied for the design mix of M20 grade concrete. The mechanical tests include compressive strength, split tensile strength and flexural strength for which the optimum percentage of replacement of ceramic waste powder and red brick dust is found. In a similar way, durability test includes acid test and corrosion test were taken for 5%, 10% and 15% replacements. The mechanical and durability test results were compared with conventional (without replacement) concrete. These tests were completed to access the mechanical properties for 7 days, 14 days and 28 days. Results showed that, mechanical properties of concrete increases for 10% effective replacement of ceramic waste powder and red brick dust. Corrosion study shows that less probability of corrosion for 10% effective replacement. Negligible loss of weight is experimented form the acid study. Thus in clear, the test results shows that, effective replacement of ceramic waste powder and red brick dust by 10% replacement to cement and 10% to fine aggregate shows contemporary results with various extends in concrete.